Impact of Braking and Speed on Current and Voltage in Electric Motorcycles: A Regression Analysis - Mawardi, Maulana; Zuriatni, Yulisya; Samsurizal, Samsurizal (Journal of Sustainable Innovation Engineering, 2025)
The development of electric vehicles is growing rapidly, including electric motorcycles as a solution to overcome the energy crisis and reduce air pollution that occurs. One important aspect is when braking and speeding which can affect the current and voltage in the vehicle's electrical system. This study aims to determine how much influence is produced when braking and speed on current and voltage. This research uses a simple regression analysis method using statistical modelling through SPSS. The results showed that there was an influence of braking and speed on the value of current and voltage produced. When braking with EBS variations of 4%, 8%, and 12% the R Square value is 96.40%, 99.80%, and 99.30% of the current. As for the voltage, the R Square value is 93.70%, 72.30%, 87.70%. The braking results of 4%, 8%, and 12% EBS variations at a speed of 10 km/h produce a current of 0.1 A, 0.5 A, 0.8 A and produce a voltage of 77.33 V, 78.47 V, 78.46 V. At the time of speed, the R Square value is 99% of the current and the R Square value is 96.20% of the voltage. Results with a speed of 10 km/h require a current of 13.5 A and produce a voltage of 77.86 V.  This study shows the influence between braking conditions and speed on current and voltage in electric motor vehicles.